Automatización del sistema de purgas en la caldera para mejorar la eficiencia térmica de funcionamiento de la generación de vapor en la empresa de embutidos La Madrileña. - Castellano Tarco, Holguer Vinicio (2018)
"Embutidos la Madrileña" company in area of steam generation, is subject to a high risk of an explosion by the build-up of steam in the boiler; internal damage to the boiler, auxiliary equipment and means of transportation of steam by the accumulation of sediments, as well as the expulsion of dissolved solid content in the boiler through the purged manual that directly affect the health of the operator and damage irreversible physical exposed to high pressure and temperature. To the provisions previously seen in the need to implement an automatic purge in the boiler system to improve the thermal efficiency of operation and safety of the workers to handle this machine. For the development and implementation of the technological proposal is based on a detailed study of the systems purges in kettles, the selectivity of the appropriate components for automation, automated methodologies supported by technical data for improvement of the thermal efficiency of the Cauldron. With the implementation of this project we improve the thermal efficiency of boiler operation to 5% balancing steam for different areas of the company, and in turn by the automatic purge system safeguard the health and life of the operator also avoid economic losses at the company.